THE INFLUENCE OF INFRASTRUCTURE LEARNING MOTIVATION STRATEGIES ON STUDENT ACHIEVEMENT SMP NEGERI 2 CAMPALAGIAN MANDAR POLEWALI DISTRICT - Nadirah, Nadirah; Sultan, Salim; Asri, Asri (UNM Geographic Journal, 2022)
This study aims to examine the effect of learning strategies, learning motivation, infrastructure on student achievement in SMP Negeri 2 Campalagian, Polewali Mandar district. This study uses quantitative methods using primary data obtained from questionnaires. The population in this study were teachers of SMP Negeri 2 Campalagian, Polowali Mandar Regency. The number of samples in this study was 39 respondents. The analytical tools used include validity and reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis tests, f tests, t tests, and R² tests. Based on the results of data analysis, it can be concluded that: the variables of learning strategy, learning motivation, and infrastructure have an effect on student achievement at SMP Negeri 2 Campalagian, Polewali Mandar Regency.